The Effect Of Sqrc (State Question Read Conclude) Technique Towards Students’ Reading Comprehension - Tawali, Tawali (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research was aimed to know The Effectiveness of SQRC Technique Towards Students’ in Reading Comprehension at the Second grade students of SMP Nurul Madinah . The design of this research was pre experimental research with one group pre-test post-test design. The population of this research was second grade students’ consist of 1 class, the class was consisted of 20 students. So, the total sample of this research was 20 students. The data were collected by using pre-test and post-test. Experimental class was treated by using SQRC learning model that used to analyze the data was t-test formula. From the data analysis, it was found that the result of t-test (4.53) was higher than t-table (1.725). The mean score of pre-test of experimental group was (71.6), and the mean score of post-test of experimental group was (77). Based on the result above, the researcher concluded that The Effectiveness of SQRC Technique Towards Students’ in Reading Comprehension at the Second grade students of SMP Nurul Madinah . It means that alternative hypothesis (Ha) is accepted and null hypothesis (H0) is rejected.